Author Correction: Neoadjuvant immune checkpoint blockade in high-risk resectable melanoma. (December 2018) - Amaria, Rodabe; Reddy, Sangeetha; Tawbi, Hussein; Davies, Michael; Ross, Merrick; Glitza, Isabella; Cormier, Janice; Lewis, Carol; Hwu, Wen-Jen; Hanna, Ehab; Diab, Adi; Wong, Michael; et al.
In the version of this article originally published, there was an error in Fig. 2b. RECIST ORR and pCR were both listed as 25%. RECIST ORR was actually 73%, and pCR was 45%. Also, an author's name was incorrect in the author list. Danny K. Wells should have been listed as Daniel K. Wells. The errors have been corrected in the print, HTML and PDF versions of this article.